My Experiences with Mathematics Education - Aaloka, (Voices of Teachers and Teacher Educators, 2016)
Most adults when asked about their experience with mathematics would say that they are scared of it. This article tries to look at some of the reasons why this is the case. It is based on some of the experiences I have had while working with children, teachers and teacher-students.